Formal gardens with Manufactures Building at right, Alaska Yukon Pacific Exposition, Seattle, 1909. - Nowell, Frank H., 1864-1950 (1909)
View of Rainier Vista, Manufactures Building in background. Caption on image: x2127 PH Coll 727.124 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number